Effects of soy isoflavone genistein on orthodontic tooth movement in guinea pigs - Sri Suparwitri; Pinandi Sri Pudyani; Sofia Mubarika Haryana; Dewi Agustina (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Osteoblast and osteoclast are the important factor in periodontal tissue remodeling for the orthodontic treatment success. Resorption process takes place in compression area by osteoclast and apposition in the tension area by osteoblast. In general hormone condition and age affect remodeling process. Estrogen has a high contribution in remodelling process and decreased in elderly individual such as menopausal women. Soybean contains isoflavone genistein which has similar structure and activity to estrogen. Many researchers indicate that isoflavone genistein not only has an inhibitor effect in osteoporosis but also has estrogenic and antiestrogenic effect as well. Purpose: The study aimed to investigate the effect of soybean isoflavone genistein administration on osteoblast and osteoclast cells number in orthodontic tooth movement of young and old guinea pigs. Method: The research was quasi-experimental study with post test only with control design. The experimental animals were 24 male guinea pigs that divided into: young guinea pigs (±4 months old) and old guinea pigs (±2.5 years old). Each group was divided into 4 subgroups for receiving the treatment namely; control, orthodontic treatment, genistein treatment and orthodontic+genistein treatment. All of the subjects were sacrificed at day 7 and the specimens were histologically analyzed using tartrate resistance acid phosphatase (TRAP) and hematoxylin eosin (HE) staining and observed using microscope that connected to obtilab and an image raster program. Result: U Mann-Whitney statistical analysis showed there were significant differences in osteoblast cell numbers; between orthodontic treatment and orthodontic+genistein treatment in the old guinea pigs (p=0.004); between orthodontic treatment in the young guinea pig and orthodontic+genistein treatment in the old guinea pig (p=0.016); between orthodontics treatment and orthodontic+genistein treatment in the young guinea pigs (p=0.025). U Mann-Whitney statistical analysis showed there were significant differences in osteoclast cell numbers: between the orthodontic treatment in the old guinea pig and orthodontics+genistein treatment in the young guinea pigs (p=0.007); between orthodontic treatment group in the young guinea pigs and orthodontics+genistein treatment in the old guinea pigs; between orthodontic treatment and orthodontic+ genistein treatment in the young guinea pigs (p=0.007). All groups administered by genistein the numbers of osteoblast in the surrounding of the tension sites increased, while in the surrounding of the compression sites had less osteoclasts; even, there were no osteoclasts found in some samples. Conclusion: Soybean isoflavone genistein administration on orthodontic tooth movement increased osteoblast numbers in the tension sides and decreased osteoclast numbers in the compression sides.